Toward Two‐Dimensional π‐Conjugated Covalent Organic Radical Frameworks. (30th May 2018) - Wu, Shaofei; Li, Minchan; Phan, Hoa; Wang, Dingguan; Herng, Tun Seng; Ding, Jun; Lu, Zhouguang; Wu, Jishan
Abstract: Reported is the synthesis, characterization, and material properties of the first π‐conjugated two‐dimensional covalent organic radical framework (CORF), PTM‐CORF, based on the stable polychlorotriphenylmethyl (PTM) radical. The covalent organic framework (COF) precursor (PTM‐H‐COF ) was first synthesized by liquid/liquid interfacial acetylenic homocoupling of a triethynylpolychlorotriphenylmethane monomer, and showed crystalline features with a hexagonal diffraction pattern matching that of A‐B‐C stacking. Subsequent deprotonation and oxidation of the PTM units in PTM‐H‐COF gave PTM‐CORF . Magnetic measurements revealed that the neighboring PTM radicals in the PTM‐CORF are anti‐ferromagnetically coupled each other, with a moderate exchange interaction ( J =−375 cm −1 ). The PTM‐CORF has a small energy gap (ca. 0.88 eV) and a low‐lying LUMO energy level (−4.72 eV), and exhibits high electrocatalytic activity and durability toward the oxygen reduction reaction.